Educação matemática no curso de Pedagogia: uma proposta com histórias virtuais na perspectiva da atividade orientadora de ensino - Silva, Henrique Fernandes da (2024)
This dissertation is part of the research line "Teaching, Knowledge, and Professional Development" of the Graduate Program in Education at the Federal University of Santa Maria and stems from the following problem: "What can we understand from the ways of producing meaning in the learning process of pre-service teachers who will teach mathematics through the creation of Virtual Stories?" To address this, the objective was to understand the learning process of teaching for future teachers who will teach mathematics by organizing Virtual Stories from the perspective of Teaching-Oriented Activity. The research was conducted with fifteen future teachers enrolled in the course Mathematical Education A, during the 6th semester of the evening Pedagogy program at the Federal University of Santa Maria. The theoretical and methodological foundation was based on Cultural-Historical Theory, represented by Lev Semionovitch Vygotsky, and more specifically on Activity Theory, from the perspective of Alexis Nikolaevich Leontiev, and Teaching-Oriented Activity, by Manoel Oriosvaldo de Moura. Data collection was carried out through audio recordings of the classes, written productions of the participants, two questionnaires answered by them, and a researcher's diary. For data analysis, in addition to Teaching-Oriented Activity, the Semantic Fields Model, developed by Romulo Campos Lins, aided in the reading of the utterances produced by the pre-service teachers, organized into axes, episodes, and scenes. In the episodes, we analyzed the completeness of each axis, highlighting the scenes that allowed the participants' utterances to stand out. At the end of the research, it was identified that the participants have an aversion to Mathematics, but that the presented Virtual Story can be a means to overcome this. The participants intended to contextualize their Virtual Stories in scenarios with plausible access to knowledge for the hypothetical children. It was also found that when discussing knowledge production for a theory, pre-service teachers may use different vocabularies, based on already internalized concepts, to approach theoretical objects. Based on this, we hypothesize that undergraduate students create a "singular interlocutor," aimed at "talking about pedagogical matters" without distinguishing between authors. Furthermore, we found that difficulties with the production of Virtual Stories may not only be related to theoretical depth but also to creative writing.